2018
DOI: 10.1007/s00359-018-1255-3
|View full text |Cite
|
Sign up to set email alerts
|

Tyraminergic modulation of agonistic outcomes in crayfish

Abstract: Octopamine, a biogenic amine, modulates various behaviors, ranging from locomotion and aggression to learning and memory in invertebrates. Several studies recently demonstrated that tyramine, the biological precursor of octopamine, also affects behaviors independent of octopamine. Here we investigated the involvement of tyramine in agonistic interaction of the male crayfish Procambarus clarkii. When male crayfish fight, larger animals (3-7% difference in body length) are more likely to win. By contrast, direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Remarkably, both the formation of social relationships and complex behavioural integrations were performed by balancing similarly diverse subsets of transmitters [37,[79][80][81][82][83][84][85][86] as in early branching animal lineages. Thus, the broadest spectrum of nearly all studied behaviours is inherently traced to multiple transmitter pathways, and the transmitter organization as well as synaptic and non-synaptic integration of behaviors are intrinsically embedded in every neural circuit from a comb jelly to Octopus.…”
Section: Convergent Evolution and Diversity Of Neural Systems In Metazoamentioning
confidence: 99%
“…Remarkably, both the formation of social relationships and complex behavioural integrations were performed by balancing similarly diverse subsets of transmitters [37,[79][80][81][82][83][84][85][86] as in early branching animal lineages. Thus, the broadest spectrum of nearly all studied behaviours is inherently traced to multiple transmitter pathways, and the transmitter organization as well as synaptic and non-synaptic integration of behaviors are intrinsically embedded in every neural circuit from a comb jelly to Octopus.…”
Section: Convergent Evolution and Diversity Of Neural Systems In Metazoamentioning
confidence: 99%
“…The a priori contrast was significant for tyrr1 . Tyramine is associated with decreased aggression for arthropods (Momohara et al., 2018 ; Szczuka et al., 2013 ), so decreasing a receptor could increase aggression. We were able to recapitulate previously observed decrease between octopamine α receptor and octopamine/tyramine receptor 1 expression and a female during Resource Preparation (Cunningham et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence has shown that agonistic behavior depends on the release of amines with a neurotransmitter function, such as tyramine [ 82 ], octopamine, and serotonin. Serotonin induces an increase on the number and intensity of agonistic encounters in crayfish [ 83 ].…”
Section: Circadian System Coupling: Possible Role Of Mel In Behavimentioning
confidence: 99%